PENGUKURAN PENGGUNAAN E-LEARNING PADA SMK–SMAK BOGOR DENGAN TECNOLOGY ACCEPTANCE MODEL (TAM) - Fety Febriyanti; Kudiantoro Widianto (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
The implementation of e-learning in SMK-SMAK Bogor since the 2012-2013 school year. The E-learning consists of learning materials, matter (assignment), exams and can also communicate between students and teachers. This study aims to determine the factors that influence students' attitudes in accepting the use of e-learning in Vocational High School - SMAK Bogor. Variables used in this research is the ease of use and benefit by using the Technology Acceptance Model (TAM). Data collection methods used are observation, interviews, library research, and questionnaires. Total population is taken as many as 273 students of class XI and the respondent sample used in this study were as many as 73 students, is calculated using the formula Slovin with 10% significance. This type of sampling used was probability sampling with simple random sampling technique. In this study, the quantitative analysis used multiple regression analysis. Based on the analysis of the data showed that 12.8% of students who accept the existence of e-learning technology based on the ease and benefits of e-learning. The results of these two hypotheses being tested, H1: Ease of use of e-learning influence the attitudes of the users of e-learning. H2: Benefits of e-learning did not affect the user's e-learning attitude. This is because the significant value of the benefit is greater than 5% (0.46 > 0.05).